2019
DOI: 10.1557/jmr.2019.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidation on thermal fatigue behavior of cast tungsten carbide particle/steel substrate surface composite

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The chemical composition of the interface ( point 2 in Fig. 6(a) ) is 26.28 at.% Fe + 72.01 at.% W, the atomic number ratios of Fe and W are all close to 1: 1, combining with the XRD pattern shows that it is Fe 3 W 3 C, that is WC particle edge melting W 2 C reacts with Fe to form interface Fe 3 W 3 C [17]:…”
Section: Resultsmentioning
confidence: 91%
“…The chemical composition of the interface ( point 2 in Fig. 6(a) ) is 26.28 at.% Fe + 72.01 at.% W, the atomic number ratios of Fe and W are all close to 1: 1, combining with the XRD pattern shows that it is Fe 3 W 3 C, that is WC particle edge melting W 2 C reacts with Fe to form interface Fe 3 W 3 C [17]:…”
Section: Resultsmentioning
confidence: 91%
“…When the average particle size of WC powder is 200 nm, it can be seen that W, Fe and Co elements have obvious diffusion at the interface in the transition region, as shown in Figure 9a. Shan [20] studied the microstructure of the composite interface of tungsten carbide-reinforced surface composites with Figure 9 is the SEM micrograph and EDS image of the interface of WC/HSS composites prepared using tungsten carbide powder with particle sizes of 200 nm and 500 nm at 1300 • C. Using the same sintering temperature of 1300 • C, the left side of the image is WC and the right side is M2 high-speed steel. The main elements detected by surface scanning are Fe, W, Cr and Co.…”
Section: Composite Interface Microstructure and Element Diffusionmentioning
confidence: 99%
“…When the average particle size of WC powder is 200 nm, it can be seen that W, Fe and Co elements have obvious diffusion at the interface in the transition region, as shown in Figure 9a. Shan [20] studied the microstructure of the composite interface of tungsten carbide-reinforced surface composites with different particle sizes. It was found that the solubility of tungsten carbide particles in the matrix decreased with the increasing of the size of tungsten carbide particles.…”
Section: Composite Interface Microstructure and Element Diffusionmentioning
confidence: 99%